REINFORCED STRUCTURE FOR HOOKS (2012)
A reinforced hook structure may include a hook body, having a back board which is a curved hook portion made in one piece, and a space is formed between the top portion of the hook portion and the back board to engage with a hanging unit. The front portion of the hook portion and the back board has some reinforced ribs, while the inner portion of the hook portion and the back board has a reinforced section to enhance the structural strength between the hook portion and the back board. When the hanging portion wedges in the hanging unit to hang subjects, the hanging portion has to sustain the weight of the subject and the hanging unit and when the hanging portion is weaker, it may be bended or broken.